An analysis of the process of disinflationary structural change: The case of Mexico - Daniel Vaughan (Banco de México, 2013)
I study the diffusion process of permanent disinflationary shocks in the Mexican economy using disaggregated price data for 283 goods across 46 cities in the period 1995-2012. I first show that the distribution of shocks shows considerable heterogeneity, with more than 80% of all cases having experienced a break. I then show that both the likelihood and timing are spatially correlated across cities, and find a positive and concave relationship between CPI weights and the likelihood and timing of a break. These findings suggest that the process of structural change follows a diffusion process across the spatial and goods dimensions.
Keywords: E30; E31; N16; N26; O54; C21; C22; C24; 330; structural change; inflation; spatial econometrics; trend-stationary; emerging economy; Mexico